The correlation between self-efficacy, self-confidence, and metacognitive skills on biology learning outcomes of student’s high school - Rahmawati; Daud, Firdaus; Bahri, Arsad (Biosfer: Jurnal Pendidikan Biologi, 2024)
metacognitive skills and learning outcomes of class . This research is an ex-post facto type of quantitative research with data collection carried out using self-efficacy, self-confidence and metacognitive skills questionnaires, as well as first semester Biology cognitive learning scores. The sample determination method used is the Area Proportional Random Sampling technique, so the research sample a total of 301 students and the research population was all class XI students of SMAN Polewali Mandar Regency for the 2023/2024 academic year. The data was analyzed descriptively and inferentially. The results of the research show that the self-efficacy, metacognitive skills and learning outcomes of students are in the medium category, and the self-confidence of students is in the high category, and there is a fairly strong relationship between self-efficacy and student learning outcomes, a very strong relationship between self-confidence and learning outcomes, a strong relationship between metacognitive skills and learning outcomes, and a very strong relationship between self-efficacy, self-confidence, and metacognitive skills and student learning outcomes. As for future researchers, it is hoped that they will use more variables and the results of this study are not in accordance with Bandura's theory that self-efficacy is always directly proportional to self-confidence, so it is necessary to study further the factors that influence students' self-confidence.